2017
DOI: 10.2340/16501977-2210
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgery exercise and post-operative physical function of people undergoing knee replacement surgery: A systematic review and meta-analysis of randomized controlled trials

Abstract: Despite a potential for efficacy of exercise-based conditioning, this review highlights the scarcity of robust dose-response evidence to guide the formulation of total knee arthroplasty prehabilitation effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 76 publications
1
26
1
Order By: Relevance
“…Conversely, length of stay was comparable between groups, although only one study reported these data. As in previous review works, these results do not achieve clinical relevance, although most are statistically significant [23,24].…”
Section: Main Interventioncontrasting
confidence: 42%
“…Conversely, length of stay was comparable between groups, although only one study reported these data. As in previous review works, these results do not achieve clinical relevance, although most are statistically significant [23,24].…”
Section: Main Interventioncontrasting
confidence: 42%
“…Pre‐operative rehabilitation interventions (or “prehabilitation”) for the purposes of improving post‐operative recovery have received considerable interest. Our search identified nine systematic reviews including 14 randomised trials. Interventions included a heterogeneous group of exercise programs, including physiotherapist supervised and unsupervised exercise, coupled with co‐interventions including acupuncture, kinesiology and education .…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
“…Interventions included a heterogeneous group of exercise programs, including physiotherapist supervised and unsupervised exercise, coupled with co‐interventions including acupuncture, kinesiology and education . While two reviews found marginal benefits to length of stay and knee range of motion, and one review demonstrated a dose–response benefit to several physical outcome measures, there was little benefit when a GRADE (Grading of Recommendations Assessment, Development and Evaluation) assessment of the evidence was performed . Twelve of 14 trials were found to have a high risk of bias, and only small, short term benefits were found for pain (100‐point scale mean difference, − 6.1; 95% CI, − 10.6 to − 1.6) and patient‐reported function (mean difference, 4.0; 95% CI, 7.5–0.5).…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
“…Previous reviews have focused on outcomes relating to preoperative function and pain, the in-hospital experience and long-term recovery 10 12–46. Review conclusions vary based on the outcomes and follow-up times.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic literature search of MEDLINE, Embase, PsycINFO, CINAHL and The Cochrane Library on 18 December 2018, we identified 36 systematic reviews of preoperative interventions in TKR. Twenty-five of these had searches conducted more than 5 years previously,10 12–35 and nine exclusively reported short-term outcomes (3 months or less after surgery) 36–44. Two more recent reviews considered the outcome of long-term pain45 46 but neither had a registered protocol.…”
Section: Introductionmentioning
confidence: 99%